Arsenic Removal from Natural Groundwater by Electrocoagulation Using Response Surface Methodology - A. M. García-Lara; C. Montero-Ocampo; F. Equihua-Guillen; J. E. Camporredondo-Saucedo; R. Servin-Castaneda; C. R. Muñiz-Valdes (Journal of Chemistry)
Contamination of natural groundwater by arsenic (As) is a serious problem that appears in some areas of Northern Central Mexico (NCM). In this research, As was removed from NCM wells groundwater by the electrocoagulation (EC) technique. Laboratory-scale arsenic electroremoval experiments were carried out at continuous flow rates between 0.25 and 1.00 L min−1 using current densities of 5, 10, and 20 A m−2. Experiments were performed under galvanostatic conditions during 5 min, at constant temperature and pH. The response surface methodology (RSM) was used for the optimization of the processing variables (flow rate and current density), response modeling, and predictions. The highest arsenic removal efficiency from underground water (99%) was achieved at low flow rates (0.25 L min−1) and high current densities (20 A m−2). The response models developed explained 93.7% variability for As removal efficiency.